Prevalence Of Allergic Rhinitis And Its Association With Asthma In Urban Populations. - Hafeez, Muhammad; Ullah, Aziz; Ali, Farman; ud Din Shinwari, Wajih; Iqbal, Arshad; Ahmad, Siyyar (Journal of Neonatal Surgery, 2025)
ABSTRACT Background:Allergic rhinitis (AR) is a prevalent chronic condition in urban communities, often underdiagnosed despite its significant health and economic burden. It shares pathophysiological mechanisms with asthma, forming the concept of a “united airway.” Recognizing prevalence patterns and associations with asthma can guide integrated screening and management strategies in urban populations. Objectives:To determine the prevalence of allergic rhinitis in an urban population and to analyze its association with physician-diagnosed asthma, highlighting the burden of united airway disease in city residents. Study Design: A Prospective Study. Place and duration of study: Department of ENT, Pak International Medical College Peshawar, from June 2024 to July 2025. Methods: This prospective study was conducted among 100 adults from randomly selected households in an urban area. Allergic rhinitis was diagnosed using ARIA criteria, while asthma was defined by physician diagnosis and validated symptom questionnaires. Data were collected through structured interviews and analyzed using SPSS v24.0. Prevalence estimates were calculated, and associations were tested with chi-square and logistic regression, reporting odds ratios with 95% confidence intervals and p-values <0.05. Results: Out of 100 participants, 53 (53.0%) were male and 47 (47.0%) female. The mean age was 34.8 ± 10.6 years. The prevalence of allergic rhinitis was 28.7% (95% CI: 23.5–33.9). Asthma was present in 12.3% of participants. Allergic rhinitis was significantly associated with asthma (p=0.002). Logistic regression revealed that participants with AR had 2.6 times higher odds of having asthma (OR=2.61, 95% CI: 1.37–4.95). The findings support the “united airway” hypothesis and emphasize early recognition and integrated disease management strategies. Conclusion:Allergic rhinitis was common in this urban population and demonstrated a strong association with asthma. The findings underscore the importance of screening for both conditions in city health programs. Integrated strategies addressing upper and lower airway diseases may improve overall disease control, reduce morbidity, and enhance quality of life. Early interventions are recommended to prevent progression and optimize health outcomes in vulnerable urban communities..